KIF5A and ALS2 Variants in a Family With Hereditary Spastic Paraplegia and Amyotrophic Lateral Sclerosis - Simone, Marta; Trabacca, Antonio; Panzeri, Elena; Losito, Luciana; Citterio, Andrea; Bassi, Maria Teresa (Frontiers in Neurology, 2018)
This paper describes the clinical evolution and the novel genetic findings in a KIF5A mutated family previously reported as affected by spastic paraparesis only. The additional evidence we report here, a homozygous ALS2 mutation detected in the proband, and the clinical evolution observed in the affected members of the family, are in line with the evidence of an overlap between Hereditary Spastic Paraplegias and Amyotrophic Lateral Sclerosis associated with variants in these genes. The proband, a 14-years-old boy, started manifesting a pure form of HSP at age 14 months. The disease rapidly progressed to a juvenile form of ALS. This boy carries a heterozygous missense variant in KIF5A p.(Glu755Lys), inherited from the father, and a homozygous missense variant in the alsin protein encoded by the ALS2 gene p.(Pro192Leu). The father shows a family history of ALS. In the last few years, he has been developing signs and symptoms of both upper and lower motor neuron degeneration, with mild bulbar motor involvement and emotional lability. The patients described in this family, confirm the continuum and partial overlap of the two clinical entities, HSP and ALS, historically viewed as distinct entities. The genetic findings in this family further substantiate the genetic bases underlying the overlap, broadening the clinical spectrum associated with KIF5A mutations.